2004
DOI: 10.1152/physrev.00014.2003
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Potentiation and Memory

Abstract: Lynch, MA. Long-Term Potentiation and Memory. Physiol Rev 84: 87–136, 2004; 10.1152/physrev.00014.2003.—One of the most significant challenges in neuroscience is to identify the cellular and molecular processes that underlie learning and memory formation. The past decade has seen remarkable progress in understanding changes that accompany certain forms of acquisition and recall, particularly those forms which require activation of afferent pathways in the hippocampus. This progress can be attributed to a numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
1,118
0
31

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,684 publications
(1,177 citation statements)
references
References 665 publications
(487 reference statements)
28
1,118
0
31
Order By: Relevance
“…In a mouse study, rolipram-induced increases of cAMP reduce the spatial memory defects associated with aging (Bach, Barad et al 1999). The cAMP cascade is one of several implicated in studies of long term potentiation (LTP), a neuronal model of memory (Lynch 2004). LTP is considered a form of synaptic plasticity based on synaptic strengthening which is known to involve cAMP (Frey, Huang et al 1993;Weisskopf, Castillo et al 1994), AMPA receptors, and NMDA receptors.…”
Section: Camp In Memorymentioning
confidence: 99%
“…In a mouse study, rolipram-induced increases of cAMP reduce the spatial memory defects associated with aging (Bach, Barad et al 1999). The cAMP cascade is one of several implicated in studies of long term potentiation (LTP), a neuronal model of memory (Lynch 2004). LTP is considered a form of synaptic plasticity based on synaptic strengthening which is known to involve cAMP (Frey, Huang et al 1993;Weisskopf, Castillo et al 1994), AMPA receptors, and NMDA receptors.…”
Section: Camp In Memorymentioning
confidence: 99%
“…It has been suggested that this effect may reflect a decrease in the nitric oxide synthase activity, and concomitantly in reduced nitric oxide levels. Since glutamate and nitric oxide are closely linked in pathways associated with long-term potentiation (Bliss and Collingridge, 1993;Lynch, 2004). Since long-term potentiation is assumed to represent a physiological model for learning and memory (Lynch, 2004), this might be a potential mechanism underlying cognitive deficits in a TRP deficiency model.…”
Section: Neurochemical Mechanisms Involved In the Effects Of 5-ht 6 Amentioning
confidence: 99%
“…Since glutamate and nitric oxide are closely linked in pathways associated with long-term potentiation (Bliss and Collingridge, 1993;Lynch, 2004). Since long-term potentiation is assumed to represent a physiological model for learning and memory (Lynch, 2004), this might be a potential mechanism underlying cognitive deficits in a TRP deficiency model. As mentioned earlier, 5-HT 6 antagonists seem to increase excitatory neurotransmission (Dawson et al, 2001).…”
Section: Neurochemical Mechanisms Involved In the Effects Of 5-ht 6 Amentioning
confidence: 99%
“…synaptic plasticity | hippocampus | immediate-early gene | reconsolidation A fundamental question in neuroscience concerns the cellular mechanisms that lead to long-term memory (LTM) formation (1)(2)(3). It has been shown that LTM formation is associated with and demands strengthening of existing synapses, socalled functional plasticity (3)(4)(5), but it may also be linked with a more overt form of structural plasticity, an increase in synapse density (6)(7)(8)(9).…”
mentioning
confidence: 99%